DISTRIBUTION OF INCIDENCE OF ONCOLOGY, DIGESTIVE, ORTHOPEDIC AND TRAUMATOLOGY CASES BY AGE AT THE PADANG SPECIAL SURGERY HOSPITAL - Yastori Yastori (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2021)
Padang City Special Surgery Hospital is a hospital that consists of several surgical services including orthopedic, oncology, urology, digestive, medical rehabilitation and chemotherapy services. The three highest incidents in 2018 were oncology cases with 865 cases (27.97%), digestive with 402 cases (13.00%), and orthopedics and traumatology with 971 cases (31.39%) in 2018. This study aims to know the description of the incidence of oncology, digestive, orthopedic and traumatology cases based on age groups at the Padang Special Surgery Hospital in 2018. The design of this study is a retrospective descriptive based on the medical records of all patients in 2018. The population used is all patient medical record files in 2018. 3,093 medical record files. From the results of this study, it is known that oncology cases based on age groups have the highest incidence in early elderly (45-55 years) as many as 152 cases (17.57%) while the lowest incidence in children under five (0-5 years) is 3 cases (0.35). %), digestive cases based on age group with the highest incidence in early elderly as many as 76 cases (18.91%) while the lowest incidence in children under five was 2 cases (0.50%), orthopedic and traumatology cases based on age group with the highest incidence. in the late elderly (56-65 years) 200 cases (20.60%) the lowest incidence in under-fives was 12 cases (1.24%).